Groundwater Potency Analysis Using Remote Sensing and Analytical Hierarchy Process To Overcome Drought In Rembang Regency, Indonesia - Putranto, Thomas Triadi; Mustiono, Ady Rieo Wahyu; Hidayatillah, Ahmad Syauqi (Faculty of Geography, Universitas Gadjah Mada, 2024)
Water is an indispensable need for all living beings, including humans, who require this vital resource for consumption, bathing, and agricultural irrigation. One of the sources of clean water is groundwater, which meets 80% of the drinking needs. However, only 82.1% of the population in Central Java has access to clean water, while the remaining 17.9% have limited accessibility. This condition was caused by the prevalence of droughts, particularly in Rembang Regency, indicating that several efforts are needed to overcome this problem. Therefore, this study aims to analyze the groundwater potential in Rembang Regency using remote sensing and Analytical Hierarchy Process (AHP) methods. The remote sensing technique was used to determine the lithology, hydrogeology, lineament density, slope, rainfall, vegetation cover, and land use of the area, while the AHP method was utilized to assess groundwater potential. The results showed that the hydrogeology parameter had the greatest influence with a weight of 21.8%, followed by lithology (15.8%), rainfall (15.1%), vegetation cover (13.5%), land use (10.9%), lineament density (14%), and slope (9.4%). These findings were then validated with existing points of interest, including dug wells, deep wells, and reservoirs. The analysis results showed that the study area can be divided into 4 zones based on the groundwater potential, namely very low (1.2 – 2.24), low (2.24 – 3.48), moderate (3.48 – 4.72), and high (4.72 – 5.96) with areas of 0.19 km2, 234.8 km2,173.4 km2, and 51.9 km2, respectively. Furthermore, based on the validation, 90 out of 108 (83%) interest points were in line with the groundwater potential map zones.